Effect of copper on tensile strength improvement of Al-Cu-SiCp new composite - Maleque, Md. Abdul; Arifutzzaman, Abul (Trans Tech Publications, 2014)

(untitled)
The aim of this paper is to improve the tensile strength of Al-Cu-SiCp composite by varying the percentage of Cu in the matrix. The composite materials with 2, 4 and 6 % Cu were developed using a noble stir casting method. Tensile test was conducted using universal tensile test machine according to ASTM-2002 (E8M-01) standard and the fracture surface was analysed using scanning electron microscope (SEM). The result showed that the ultimate tensile strength (UTS)was increased due to the percentage increment of Cu in the Al-Cu matrix. A significant change in UTS was observed from 2 to 4 % Cu whereas slight improvement was seen from 4 to 6 % Cu addition. The SEM micrograph of the fracture surface reveals that the cracks were propagated in the fibrous zone resulting from the initiation of micro voids between the matrix and particle interfaces. The number and size of dimples for 2% Cu were considerably lower and the facet features were noticeably higher than higher Cu content composition, whereas, the dimple and facet size and number for the 4% Cu are very close to the 6% Cu content composite which may play important role in the improvement of tensile strength. These findings tinted for the potential application of SiCp reinforced Cu influenced Al-Cu-SiCp composite for automotive engine components and other similar applications as well.